HUMILITY DI DALAM KEPEMIMPINAN LEMBAGA PENDIDIKAN ISLAM - Samsul Arifin, Budi Haryanto (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2020)
This research is an attempt to describe Humility when it comes to leadership in Islamic educational institutions. The question in this research that you want to answer is the type of leadership Humility? To answer this question, researchers used data sources obtained from libraries, articles, and scientific journals. The findings in this study are that one of the Humility leadership has a type: know who doesn't know, is not afraid to fail because of puberty, does not underestimate competition, embraces and encourages the spirit of serving, listens to ideas, is eager to always be curious